THE STAR TIME – DEITIC MARKS IN THE IDENTITY BUILDING - Marques da Silva, Márcia Breguês (2007)
This essay intends to analyze throughout linguistic and discursive readingsthe building of identity in the novel A Hora da Estrela by Clarice Lispector. We shall investigate the application of Deixis as a speaker ideological position marker , constitutedin the enunciation, concerned about the other, evidencing the social segregation in thenarrative. In our interpretative effort, we shall observe that deictic words permeate theenvironmental representative speeches which point to the principal of the work, Macabéa,characterizing her like an unconscious and a marginalized human being, therefore, raisingdifficulties during her process of identity formation. The theoretical grounding thatsupports this analysis is chiefly based on the study of the linguistic phenomena developedby the following authors: Émile Benveniste, Catherine Kerbrat-Orecchioni, DominiqueMaingueneau e Mikhail Bakhtin.